The antibacterial effectiveness of lavender essential oil against methicillin-resistant Staphylococcus aureus: a systematic review - Truong, Sandra; Mudgil, Poonam (Frontiers in Pharmacology, 2023)
With the overuse and misuse of antibiotics, multi-drug resistant organisms have become a prominent issue in healthcare, increasing morbidity and mortality in affected patients. One such organism of concern is methicillin-resistant Staphylococcus aureus (MRSA) which is a leading cause of a variety of clinical infections. Therefore, in the interest of finding alternate substances to antibiotics, there has been increased interest in the antibacterial properties of lavender essential oil (LEO). This systematic review aims to collate information regarding the antibacterial properties of LEO against S. aureus and MRSA. A systematic search was conducted across four databases between the years 2002 and 2022, and through this, 23 studies were included in this paper. These studies used a variety of methods to ascertain the antibacterial effectiveness of LEO alone or in combination with other substances. Overall, there were mixed results regarding the antibacterial effectiveness of LEO against S. aureus and MRSA, with some studies reporting significant effectiveness, while other studies reporting a minimal to negligible effect. However, findings suggest that LEO works synergistically with other antibacterial substances, and it would be beneficial for additional research to be conducted in this area.